Penerapan Empat Kata Ajaib Sebagai Bentuk Peningkatan Moral Siswa di UPT SDN 060921 Medan Sunggal - Citra Mutiara Nst; Fajar Utama Ritonga (Yayasan Literasi Sains Indonesia, 2023)
Elementary school education can strive to educate and print the life of a nation that is pious, loves and is proud of the nation and country, is skilled, creative, has good character and manners. This education has a role in building the knowledge base of students to be used in further education. As a place for children to study, children also need to be taught manners and manners or good moral attitudes, because manners are very important for each individual in everyday life. Moral is a teaching about good and bad deeds and behavior, morals that everyone has. Moral can be divided into two, namely good morals and bad morals. Seeing the situation where there are still many students who have not used the 4 magic words properly, it is necessary to apply the four magic words namely sorry, please, thank you, and excuse me to students. The target to be achieved is to maximize and increase the use of the four magic words in the school environment for both peers and teachers or those who are older. This was also done using the casework method by Skidmore, Thackeray and Farley. The results obtained from this activity are progress in using the four magic words well with friends in the school environment.